Impact of generics competition on prices and utilization of antiepileptic medicines in Bulgaria - Manoela Manova, Zornitsa Emilova Mitkova, Alexandra Savova, Anna Borisova, Lily Peikova, Javor Mitkov, Guenka Petrova (Journal of Applied Pharmaceutical Science, 2023)
Epilepsy is one of the most common neurological disorders with significant economic and social impact. The timely access to therapy for patients is a serious problem as defined by World Health Organization. The aim of this study is to evaluate generics availability, prices, and utilization of antiepileptic medicines in order to identify the hypothesis if the entrance of generics affects the medicines utilization and price variations in the Bulgarian market. The study is performed as a three-step retrospective observational analysis of 16 existing international nonproprietary names, reimbursed by the National Health Insurance Fund during 2014–2020. The study explores the availability of generics and trademarks, along with the utilization of antiepileptic medicines and possible differences in reference price per defined daily dose (DDD) during the observed period. The 7 years review of antiepileptic medicines placed on the market in Bulgaria showed a tendency of decreasing in the number of generic medicines and in consumption despite the stability or the reduction in reference prices per DDD. This fact indicated that different factors and the country’s environment also played an important role and have affected the overall medicines market. A comprehensive generic policy should be developed to ensure timely patient access to treatment and stable level of medicines utilization.